Boys run the riot. 1 - Gaku, Keito (Kodansha Comics, 2021)
"High schooler Ryo knows he's transgender, but he doesn't have anyone to confide in about the confusion he feels. He can't tell his best friend, who he's secretly got a crush on, and he can't tell his mom, who's constantly asking why Ryo 'dresses like a boy.' He certainly can't tell Jin, the new transfer student who looks like just another bully. The only time Ryo feels at ease is when he's wearing his favorite clothes. Then, and only then, the world melts away, and he can be his true self. One day, while out shopping, Ryo sees someone he didn't expect: Jin. The kid who looked so tough in class has the same taste in fashion as him! At last, Ryo has someone he can open up to, and the journey ahead might finally give him a way to express himself to the world."--Provided by publisher.